Effect of Hot Rolling on Texture, Precipitation, and Magnetic Properties of Strip‐Cast Grain‐Oriented Silicon Steel. Issue 12 (4th April 2016) - Wang, Yang; Zhang, Yuan‐Xiang; Lu, Xiang; Fang, Feng; Cao, Guang‐Ming; Li, Cheng‐Gang; Xu, Yun‐Bo; Misra, R. Devesh Kumar; Wang, Guo‐Dong
Abstract : An ultra‐low carbon grain‐oriented silicon steel as‐cast strip is produced by twin‐roll strip casting process, and subsequently subjected to one‐pass hot rolling, one‐stage cold rolling, primary annealing, and secondary annealing. The effect of hot rolling process on microstructure, texture, and inhibitor evolution is studied. It is shown that the precipitation behavior of AlN particles is significantly affected by the hot rolling temperature and the optimal precipitation temperature is ≈1100 °C. On the other hand, the intensity of Goss texture in hot‐rolled sheets is determined by hot rolling reduction, which is limited in the strip casting process and the hot‐rolled Goss texture is relatively weak compared to the conventional process. The primary annealed Goss texture can originate from the cold rolling process and this texture is homogeneous through the thickness, besides the inherited hot‐rolled Goss texture mainly presented in the subsurface layer. Thus, relatively strong Goss texture in primary annealed sheets is obtained. The results indicate that the hot rolling process is an efficient way to optimize the texture and precipitation in strip‐cast silicon steel, and relatively good magnetic properties can be obtained by the strip casting process. Abstract : In conventional process, the Goss texture is formed during hot rolling and mainly distributed at subsurface layer . In our study, the hot rolling reduction is limited, and the hot‐rolled Goss texture is weak. But the cold rolling process can form Goss texture and distributed homogeneously through the thickness. Thus, the primary annealed sheets had a relatively strong Goss texture.